2009
DOI: 10.1038/ijo.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and adult cardiovascular disease risk: a systematic review

Abstract: Background: Although the relationship between adult obesity and cardiovascular disease (CVD) has been shown, the relationship with childhood obesity remains unclear. Given the evidence of tracking of body mass index (BMI) from childhood to adulthood, this systematic review investigated the independent relationship between childhood BMI and adult CVD risk. Objective: To investigate the association between childhood BMI and adult CVD risk, and whether the associations observed are independent of adult BMI. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
173
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 37 publications
7
173
0
7
Order By: Relevance
“…It is plausible to hypothesis that increased vascular disease especially at the level of the brain may in turn affect memory function. Obesity results in insulin resistance [19,27,28]. Insulin has a significant role on modulation of synaptic plasticity and learning memory [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to hypothesis that increased vascular disease especially at the level of the brain may in turn affect memory function. Obesity results in insulin resistance [19,27,28]. Insulin has a significant role on modulation of synaptic plasticity and learning memory [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have clearly demonstrated an association between childhood BMI and adult disease risk, but have also highlighted a gap in the evidence base surrounding the unknown independent contribution of childhood BMI (5)(6)(7) . We therefore systematically reviewed the literature with the specific objective of assessing whether the association between childhood BMI and adult disease risk were fully dependent on adult BMI (22,23) .…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…Human data linking inflammation to insulin resistance that demonstrated inter-relations between systemic markers of inflammation (CRP) and the presence of insulin resistance in adults [4,5] and adolescents [6,7]. Obesity results in insulin resistance [8][9][10]. Although certain proportions of cardiovascular disorders are attributed to the secondary complications of obesity (e.g., hypertension, atherosclerosis, T2DM and aging), a direct deleterious effect of obesity on the cardiovascular system is now clearly evident.…”
Section: Introductionmentioning
confidence: 99%